PLD1 knockdown reduces metastasis and inflammation of fibroblast-like synoviocytes in rheumatoid arthritis by modulating NF-κB and Wnt/β-catenin pathways. (3rd October 2021) - Zhang, Zhengyu; Chen, Xi; Gao, Bo; Sun, Guomin; Wang, Yan; Wang, Junke; Zhang, Ting; Qian, Hao; Zhang, Yu; Huang, Jun; Sun, Rurong; Wu, Jiabiao; et al.
Abstract: Considered as an autoimmune disease, rheumatoid arthritis (RA) is an chronic inflammatory disorder that causes inflammation of the joints. This study is performed with the aim to clarify the expression of phospholipase D1 (PLD1) in RA and its specific regulation role of RA as well as the underlying mechanisms. In this study, s ynovial tissue samples were collected from RA patients, and RA-fibroblast-like synoviocytes (FLSs) were subsequently isolated. The expression levels of PLD1 and pathway-related proteins were detected by quantitative reverse transcription polymerase chain reaction (qRT-PCR), western blotting or immunohistochemistry (IHC). Upon shPLD1 treatment, cell viability, proliferation, migration, invasion, and the level of inflammation-related factors were measured by Cell Counting Kit-8 (CCK-8), Edu, wound healing, Transwell and enzyme-linked immunosorbent assay (ELISA). Furthermore, C-reactive protein (CRP), rheumatoid factor (RF), arthritis score and synovial tissue lesions were assessed by collecting the blood or tissues from collagen induced arthritis (CIA) model rats. Our results showed that PLD1 level was increased in RA synovial tissues. Cell viability, proliferation, migration, invasion, and the level of inflammatory factors were reduced upon PLD1 knockdown in RA-FLSs. Moreover, p-IκBα/IκBα, β-catenin, p-IKKβ/IKKβ and TCF-4 were inhibited under PLD1 knockdown treatment. PLD1 knockdown alleviated the collagen-induced addition of arthritis score, CRP and RF, as well as the filling of inflammatory cells and proliferation of synovium in CIA model rat. To sum up, knockdown of PLD1 could reduce RA-FLSs metastasis as well as inflammatory response by modulating the activity of NF-κB and Wnt/β-catenin pathways.